2016
DOI: 10.1037/xlm0000150
|View full text |Cite
|
Sign up to set email alerts
|

Hitting a high note on math tests: Remembered success influences test preferences.

Abstract: Remembered utility is the retrospective evaluation about the pleasure and pain associated with a past experience. It can influence choices about repeating or avoiding similar situations in the future (Kahneman, 2000). A set of 5 experiments explored the remembered utility of effortful test episodes and how it impacted future test choices. Experiments 1-3 mimicked Kahneman, Fredrickson, Schreiber, and Redelmeier's (1993) cold pressor study, but used a challenging test experience in place of submerging one's han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 50 publications
5
50
0
Order By: Relevance
“…These results suggest that how a cognitive task ends is critically important to retrospective memories and preferences for subsequent tasks. Recently, Finn & Miele [ 18 ] provided additional evidence showing that math tests that begin or end easier are more preferred than tasks which have easier items embedded in the middle. Taken together Finn’s work suggests that both easier beginnings and endings might play key roles in determining how mentally effortful tasks are remembered.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that how a cognitive task ends is critically important to retrospective memories and preferences for subsequent tasks. Recently, Finn & Miele [ 18 ] provided additional evidence showing that math tests that begin or end easier are more preferred than tasks which have easier items embedded in the middle. Taken together Finn’s work suggests that both easier beginnings and endings might play key roles in determining how mentally effortful tasks are remembered.…”
Section: Introductionmentioning
confidence: 99%
“…A number of disparate but intriguing effects also point to the potency of success with challenge, particularly over challenge alone. For example, Finn and Miele (2015) found that test takers preferred longer tests of difficult math problems with starting or ending sets of moderately difficult (successful) items to shorter tests of the same difficult math problems only. Interestingly, in the hippocampus, learning, but not training per se, rescues or increases the survival of newly generated cells into differentiated neurons to the extent that the learning experience is new, effortful, and importantly successful (Shors, 2014).…”
Section: Mechanisms For Enhanced Expectancy Effectsmentioning
confidence: 99%
“…To conclude, this study indicates that children's memory of emotional experiences is very sensitive to endings and that the process of peer assessments can be improved by ending with the most positive aspect of the feedback. This study thereby contributes to a growing body of literature exploring practical applications of the peak-end effect in contexts relevant for learning (Finn, 2010;Finn & Miele, 2016;Hoogerheide & Paas, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…These findings beg the question whether the same mechanism applies to contexts relevant for learning. Recent studies showed that this can indeed be the case for students studying foreign vocabulary for a test (Finn, 2010;Hoogerheide & Paas, 2012) and for students taking a difficult math test (Finn & Miele, 2016).…”
mentioning
confidence: 94%